Scaling Bottom-Up IFDS Taint Analysis with Optimized Data-Flow Encoding - Schiebel, Fabian Benedikt; Bodden, Eric (40th European Conference on Object-Oriented Programming (ECOOP 2026))

Scaling Bottom-Up IFDS Taint Analysis with Optimized Data-Flow Encoding - Schiebel, Fabian Benedikt; Bodden, Eric (40th European Conference on Object-Oriented Programming (ECOOP 2026))

Distributed and Parallel Low-Diameter Decompositions for Arbitrary and Restricted Graphs - Dou, Jinfeng; Götte, Thorsten; Hillebrandt, Henning; Scheideler, Christian; Werthmann, Julian (16th Innovations in Theoretical Computer Science Conference (ITCS 2025))

Symmetry Preservation in Swarms of Oblivious Robots with Limited Visibility - Gerlach, Raphael; von der Gracht, Sören; Hahn, Christopher; Harbig, Jonas; Kling, Peter (28th International Conference on Principles of Distributed Systems (OPODIS 2024))
In the general pattern formation (GPF) problem, a swarm of simple autonomous, disoriented robots must form a given pattern. The robots' simplicity imply a strong limitation: When the initial configuration is rotationally symmetric, only patterns with a similar symmetry can be formed [Yamashita, Suzyuki; TCS 2010]. The only known algorithm to form large patterns with limited visibility and without memory requires the robots to start in a near-gathering (a swarm of constant diameter) [Hahn et al.; SAND 2024]. However, not only do we not know any near-gathering algorithm guaranteed to preserve symmetry but most natural gathering strategies trivially increase symmetries [Castenow et al.; OPODIS 2022]. Thus, we study near-gathering without changing the swarm's rotational symmetry for disoriented, oblivious robots with limited visibility (the OBLOT-model, see [Flocchini et al.; 2019]). We introduce a technique based on the theory of dynamical systems to analyze how a given algorithm affects symmetry and provide sufficient conditions for symmetry preservation. Until now, it was unknown whether the considered OBLOT-model allows for any non-trivial algorithm that always preserves symmetry. Our first result shows that a variant of Go-to-the-Average always preserves symmetry but may sometimes lead to multiple, unconnected near-gathering clusters. Our second result is a symmetry-preserving near-gathering algorithm that works on swarms with a convex boundary (the outer boundary of the unit disc graph) and without holes (circles of diameter 1 inside the boundary without any robots).
Keywords: Swarm Algorithm; Swarm Robots; Distributed Algorithm; Pattern Formation; Limited Visibility; Oblivious

Theoretical Foundations of Utility Accrual for Real-Time Systems - Chen, Jian-Jia; Shi, Junjie; Günzel, Mario; von der Brüggen, Georg; Chen, Kuan-Hsun; Bella, Peter (37th Euromicro Conference on Real-Time Systems (ECRTS 2025))

Efficient Shape Formation by 3D Hybrid Programmable Matter: An Algorithm for Low Diameter Intermediate Structures - Hinnenthal, Kristian; Liedtke, David Jan; Scheideler, Christian (3rd Symposium on Algorithmic Foundations of Dynamic Networks (SAND 2024))
This paper considers the shape formation problem within the 3D hybrid model, where a single agent with a strictly limited viewing range and the computational capacity of a deterministic finite automaton manipulates passive tiles through pick-up, movement, and placement actions. The goal is to reconfigure a set of tiles into a specific shape termed an icicle. The icicle, identified as a dense, hole-free structure, is strategically chosen to function as an intermediate shape for more intricate shape formation tasks. It is designed for easy exploration by a finite state agent, enabling the identification of tiles that can be lifted without breaking connectivity. Compared to the line shape, the icicle presents distinct advantages, including a reduced diameter and the presence of multiple removable tiles. We propose an algorithm that transforms an arbitrary initially connected tile structure into an icicle in 𝒪(n³) steps, matching the runtime of the line formation algorithm from prior work. Our theoretical contribution is accompanied by an extensive experimental analysis, indicating that our algorithm decreases the diameter of tile structures on average.
Keywords: Programmable Matter; Shape Formation; 3D Model; Finite Automaton

Scaling Interprocedural Static Data-Flow Analysis to Large C/C++ Applications: An Experience Report - Schiebel, Fabian Benedikt; Sattler, Florian; Schubert, Philipp Dominik; Apel, Sven; Bodden, Eric (38th European Conference on Object-Oriented Programming (ECOOP 2024))

A Unifying Approach to Efficient (Near-)Gathering of Disoriented Robots with Limited Visibility - Castenow, Jannik; Harbig, Jonas; Jung, Daniel; Kling, Peter; Knollmann, Till; Meyer auf der Heide, Friedhelm (Proceedings of the 26th International Conference on Principles of Distributed Systems (OPODIS))

On the Equivalence of Maximum Reaction Time and Maximum Data Age for Cause-Effect Chains - Günzel, Mario; Teper, Harun; Chen, Kuan-Hsun; von der Brüggen, Georg; Chen, Jian-Jia (35th Euromicro Conference on Real-Time Systems (ECRTS 2023))

The Structural Power of Reconfigurable Circuits in the Amoebot Model - Padalkin, Andreas; Scheideler, Christian; Warner, Daniel (28th International Conference on DNA Computing and Molecular Programming (DNA 28))

Fault-Tolerant Shape Formation in the Amoebot Model - Kostitsyna, Irina; Scheideler, Christian; Warner, Daniel (28th International Conference on DNA Computing and Molecular Programming (DNA 28))

Brief Announcement: Fault-Tolerant Shape Formation in the Amoebot Model - Kostitsyna, Irina; Scheideler, Christian; Warner, Daniel (1st Symposium on Algorithmic Foundations of Dynamic Networks (SAND 2022))

Unikernel-Based Real-Time Virtualization Under Deferrable Servers: Analysis and Realization - Chen, Kuan-Hsun; Günzel, Mario; Jablkowski, Boguslaw; Buschhoff, Markus; Chen, Jian-Jia (34th Euromicro Conference on Real-Time Systems (ECRTS 2022))

Mincut Sensitivity Data Structures for the Insertion of an Edge - Baswana, Surender; Gupta, Shiv; Knollmann, Till (28th Annual European Symposium on Algorithms (ESA 2020))
Let G = (V,E) be an undirected graph on n vertices with non-negative capacities on its edges. The mincut sensitivity problem for the insertion of an edge is defined as follows. Build a compact data structure for G and a given set S ⊆ V of vertices that, on receiving any edge (x,y) ∈ S×S of positive capacity as query input, can efficiently report the set of all pairs from S× S whose mincut value increases upon insertion of the edge (x,y) to G. The only result that exists for this problem is for a single pair of vertices (Picard and Queyranne, Mathematical Programming Study, 13 (1980), 8-16). We present the following results for the single source and the all-pairs versions of this problem. 1) Single source: Given any designated source vertex s, there exists a data structure of size 𝒪(|S|) that can output all those vertices from S whose mincut value to s increases upon insertion of any given edge. The time taken by the data structure to answer any query is 𝒪(|S|). 2) All-pairs: There exists an 𝒪(|S|²) size data structure that can output all those pairs of vertices from S× S whose mincut value gets increased upon insertion of any given edge. The time taken by the data structure to answer any query is 𝒪(k), where k is the number of pairs of vertices whose mincut increases. For both these versions, we also address the problem of reporting the values of the mincuts upon insertion of any given edge. To derive our results, we use interesting insights into the nearest and the farthest mincuts for a pair of vertices. In addition, a crucial result, that we establish and use in our data structures, is that there exists a directed acyclic graph of 𝒪(n) size that compactly stores the farthest mincuts from all vertices of V to a designated vertex s in the graph. We believe that this result is of independent interest, especially, because it also complements a previously existing result by Hariharan et al. (STOC 2007) that the nearest mincuts from all vertices of V to s is a laminar family, and hence, can be stored compactly in a tree of 𝒪(n) size.
Keywords: Mincut; Sensitivity; Data Structure

Offloading Safety- and Mission-Critical Tasks via Unreliable Connections - Schönberger, Lea; von der Brüggen, Georg; Chen, Kuan-Hsun; Sliwa, Benjamin; Youssef, Hazem; Ramachandran Venkatapathy, Aswin Karthik; Wietfeld, Christian; ten Hompel, Michael; Chen, Jian-Jia (32nd Euromicro Conference on Real-Time Systems (ECRTS 2020))

Fully-Dynamic Bin Packing with Little Repacking - Feldkord, Björn; Feldotto, Matthias; Gupta, Anupam; Guruganesh, Guru; Kumar, Amit; Riechers, Sören; Wajc, David (45th International Colloquium on Automata, Languages, and Programming (ICALP 2018))
We study the classic bin packing problem in a fully-dynamic setting, where new items can arrive and old items may depart. We want algorithms with low asymptotic competitive ratio while repacking items sparingly between updates. Formally, each item i has a movement cost c_i >= 0, and we want to use alpha * OPT bins and incur a movement cost gamma * c_i, either in the worst case, or in an amortized sense, for alpha, gamma as small as possible. We call gamma the recourse of the algorithm. This is motivated by cloud storage applications, where fully-dynamic bin packing models the problem of data backup to minimize the number of disks used, as well as communication incurred in moving file backups between disks. Since the set of files changes over time, we could recompute a solution periodically from scratch, but this would give a high number of disk rewrites, incurring a high energy cost and possible wear and tear of the disks. In this work, we present optimal tradeoffs between number of bins used and number of items repacked, as well as natural extensions of the latter measure.

Efficiently Approximating the Probability of Deadline Misses in Real-Time Systems - von der Brüggen, Georg; Piatkowski, Nico; Chen, Kuan-Hsun; Chen, Jian-Jia; Morik, Katharina (30th Euromicro Conference on Real-Time Systems (ECRTS 2018))